The Cognitive and Neural Mechanisms Underlying Learning from Errors - Khoo, Joshua Kah Meng (2023)
A cornerstone of adaptive behaviour is the capacity to learn from errors. Past research has made significant progress to understand the cognitive and neural mechanisms that underlie this form of adaptive behaviour. However, there is still more to learn concerning the performance monitoring mechanisms that sustain the adaptive responses over long periods of time. To advance our understanding in this area, I investigated the impact of errors on learning, memory, and response adjustments using behavioural and neuroimaging methods. This thesis presents evidence showing that learning from errors can be more challenging than learning from positive outcomes. However, it also reveals that highly surprising errors can enhance episodic memory. Furthermore, neuroimaging findings showed that memory enhancement is associated with changes in the activity of in a network of brain regions associated with error detection and processing. Finally, this thesis examined the functional role of increases in response latencies after typing errors and evaluated their contribution to response adaptations i typing. Overall, these investigations provide key insights into the cognitive and neural mechanisms that underlie learning from errors.